Evaluasi Terhadap Intervensi Sekolah Luar Biasa Beringin Bhakti dalam Penanganan Anak dengan Intellectual Disabilities - Siti Musyarrofah; Ayu Anggraeni; Afifah Nur Irfani; Zakiyah Ismuwardani (CV. Akademi Merdeka, 2024)
This research was conducted at the Beringin Bhakti Special Needs School (SLB) with the aim of evaluating the role of the school in serving children with mental retardation or intellectual disabilities as well as identifying collaboration between the school and parents in the service process. This research is entitled